Warstwa Sprężysta pod Działaniem Momentu Skupionego - Świtka, R. (Engineering Transactions, 1967)
The subject of the considerations in the state of displacement and stress in an elastic slab produced by a concentrated moment. The upper boundary plane of the slab is free from load, the lower one being fixed. The concentrated moment acts at any level. The result, obtained by applying the Hankel transformation, is represented in the form of a series satisfying the boundary conditions in an accurate manner.